PENGARUH EVENT PUTERI INDONESIA DAN ELVIRA DEVINAMIRA TERHADAP PERSEPSI MASYARAKAT ATAS WANITA INDONESIA - Siswi Sekar Sari; Abdy Azwar Sahi; Agatha Corintias Relation; Yudha Satrio Leksono (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2021)
Event is something that we could use in reaching a goal and create awareness towards brand and company. The development of event over the year is changing start from exhibitions, performances, until the beauty pageant or beauty contests. Indonesia's oldest beauty pageant was called Puteri Indonesia organized by Yayasan Puteri Indonesia Indonesia under the auspices of the cosmetics company PT. Mustika Ratu. In this study, researchers wanted to know whether there is influence between Event Puteri Indonesia with Elvira Devinamira as Puteri Indonesia 2014 winner of the public perception of women in Indonesia. Where researchers use the main theories Soucre Credibility Theory, and some supporting theories such as events, and perception.As a results, that the effects of the event Puteri Indonesia and Elvira Devinamira to the public perception on Indonesian women have a positive influence. It can be concluded that every woman who follows the selection of Puteri Indonesia definitely a good woman with positive attitude as well.